2012
DOI: 10.1016/j.addr.2012.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The controlled intravenous delivery of drugs using PEG-coated sterically stabilized nanospheres

Abstract: Injectable blood persistent particulate carriers have important therapeutic application in sitespecific drug delivery or medical imaging. However, injected particles are generally eliminated by the reticuloendothelial system within minutes after administration and accumulate in the liver and spleen. To obtain a coating that might prevent opsonization and subsequent recognition by the macrophages, sterically stabilized nanospheres were developed using amphiphilic diblock or multiblock copolymers. The nanosphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
199
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(206 citation statements)
references
References 66 publications
3
199
0
4
Order By: Relevance
“…The conjugation of PLGA/PLA with PEG led to the development of block copolymers in which the covalent linkage of the hydrophilic PEG shell to the core of the Np avoids the possibility of PEG removal/desorption once in contact with biological fluids [51] Other hydrophilic molecules which have been tried are Brij 78, Poloxamer F68 and Brij 68. Cavalli et al found that parenteral administration of nanoparticles of paclitaxel was more bioavailable than an i.v.…”
Section: International Journal Of Pharmaceutical and Life Sciencesmentioning
confidence: 99%
“…The conjugation of PLGA/PLA with PEG led to the development of block copolymers in which the covalent linkage of the hydrophilic PEG shell to the core of the Np avoids the possibility of PEG removal/desorption once in contact with biological fluids [51] Other hydrophilic molecules which have been tried are Brij 78, Poloxamer F68 and Brij 68. Cavalli et al found that parenteral administration of nanoparticles of paclitaxel was more bioavailable than an i.v.…”
Section: International Journal Of Pharmaceutical and Life Sciencesmentioning
confidence: 99%
“…PLA NPs exhibited an enhancement of the anti-leishmanial effects of primaquine (Muriel et al 1998). MPEG-PLA diblock copolymer has been used for intravenous drug delivery due to its biodegradability and non-toxic behavior (Gref et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Novel carriers hold great promise in achieving enhanced bioavailability, reduced cytotoxicity, targeted delivery, controlled release, and improved efficacy that can ultimately result in desired therapeutic responses in the body. Among these carriers, micro- (Kurmi et al, 2010;Leong and Wang, 2015;Skorb and Möhwald, 2014) and nano- (Gref et al, 2012;Peer et al, 2007;Schroeder et al, 2010;Wang et al, 2012) structures have attracted significant research interest because of their tunability in physical (size, structures, porosity, and mechanical strength) and chemical (compositions, reactivity, biocompatibility, and biodegradability) properties, and flexibility in integrating different functions, such as for active/passive targeting, stimuli-responsive release, and diagnostics/imaging. To enable their full potential in practical pharmaceutical applications, the development of advanced and robust platform technologies for the manufacture of microand nanostructured materials with high degree of uniformity (size, size distribution, and shape), batch-to-batch reproducibility and scale-up possibilities, becomes highly essential.…”
Section: Introductionmentioning
confidence: 99%